Sea Surface Temperature: From Observation to Applications - Pastor Guzman, Francisco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers a broad range of sea surface temperature studies from very different points of view and scales; the SST is observed from very local to regional and oceanic scales. The chapters of this book move from local and remote data sensing validation to local and regional trend analysis, and also give some insight into marine heatwaves and future climate scenarios.